AB0921 Impact of baseline demographics, disease activity and concomitant medication on american college of rheumatology 20 response rate and health assessment questionnaire-disability index score with tofacitinib in active psoriatic arthritis: a pooled subgroup analysis of 2 phase 3 studies. (12th June 2018) - Behrens, F.; Gomez-Reino, J.; Nash, P.; Gladman, D.D.; FitzGerald, O.; Ritchlin, C.; Kudlacz, E.; Wu, J.; Wang, C.; Romero, A.B.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of psoriatic arthritis (PsA). In a pooled analysis of data from 2 Phase 3 trials in patients (pts) with active PsA, tofacitinib 5 and 10 mg twice daily (BID) significantly improved American College of Rheumatology (ACR) 20 response rates vs placebo (PBO) (50.0, 53.0 vs 28.0%, respectively; p<0.001) and least squares mean (LSM) change from baseline (BL) in Health Assessment Questionnaire-Disability Index (HAQ-DI) score vs PBO (0.38, –0.38 vs −0.16, respectively; p<0.001) at Month 3. 1 Objectives: To compare the efficacy of tofacitinib 5 and 10 mg BID vs PBO in predefined pt subgroups based on differences in BL demographics, disease activity and concomitant medication. Methods: This was an analysis of pooled efficacy data from 2 Phase 3, randomised, double-blind, PBO-controlled studies (OPAL Broaden [12 months; NCT01877668 ] and OPAL Beyond [6 months; NCT01882439 ]) in pts with active PsA (defined as ≥3 swollen and ≥3 tender joints). Pts in OPAL Broaden were tumour necrosis factor inhibitor (TNFi)-naïve with an inadequate response (IR) to ≥1 conventional synthetic disease-modifying antirheumatic drug (csDMARD). Pts in OPAL Beyond had an IR to ≥1 TNFi. Pts were randomised to receive tofacitinib 5 or 10 mg BID, subcutaneous adalimumab 40 mg every 2 weeks (OPAL Broaden; data not included) or PBO. Pts continued to receive a stable dose of a single csDMARD. ACR20 response rates and LSM change from BL in HAQ-DI at Month 3 (primary endpoint data) were evaluated by subgroup category (demographic and disease characteristics at BL or at screening). Analyses were based on the full analysis set (table 1). Results: In total, 238, 236 and 236 pts received tofacitinib 5 mg BID, 10 mg BID, or PBO, respectively. Across all subgroups analysed, tofacitinib 5 and 10 mg BID were generally associated with greater improvements at Month 3 in ACR20 and change from BL in HAQ-DI score than PBO (table 1). In pts classified as current smokers, slightly lower ACR20 response rates and similar changes from BL in HAQ-DI score to corresponding PBO at Month 3 were observed relative to never- or ex-smokers; however, the sample size was small. Statistical methods: ACR20 response was defined as achieving a≥20% improvement in ACR criteria components Missing ACR20 response was considered a non-response to treatment LSMs were calculated based on a mixed model for repeated measures without imputation for missing values ACR, American College of Rheumatology; BID, twice daily; BMI, body mass index; BSA, body surface area; CRP, C-reactive protein; csDMARD, conventional synthetic disease-modifying antirheumatic drug; DSS, Dactylitis Severity Score; HAQ-DI, Health Assessment Questionnaire-Disability Index; LEI, Leeds Enthesitis Index; LSM, least squares mean; MTX, methotrexate; N, number of patients in full analysis set (randomised and received ≥1 treatment dose); n, number of responders; N1, number of patients in the full analysis set by category of subgroup and treatment; N2, number of patients included in the repeated measures model by category of subgroup and treatment; NC, analysis not conducted; PASDAS, Psoriatic Arthritis Disease Activity Score; PASI, Psoriasis Area and Severity Index; PsA, psoriatic arthritis; pts, patients; ROW, rest of world (Brazil, Mexico and Taiwan); SPARCC, Spondyloarthritis Research Consortium of Canada (enthesitis index) Conclusions: In this analysis of pooled data from 2 Phase 3 studies in pts with active PsA, tofacitinib 5 and 10 mg BID consistently improved efficacy at Month 3 compared with PBO across all predefined subgroups evaluated, with the exception of current smoking; however, as this was not a pre-specified analysis and some subgroups (including smoking status) were small, interpretation should be made with caution. Reference: [1] Nash P, et al. Arthritis Rheumatol2017;69(suppl 10):619. Acknowledgements: Study sponsored by Pfizer Inc. Medical writing support was provided by K Nicholson of CMC and funded by Pfizer Inc. Disclosure of Interest: F. Behrens Grant/research support from: AbbVie, Chugai, Novartis, Pfizer Inc, Prophylix, Roche, Consultant for: AbbVie, Biotest, BMS, Celgene, Chugai, Eli Lilly, Genzyme, Janssen, MSD, Novartis, Pfizer Inc, Roche, UCB, Speakers bureau: AbbVie, Biotest, BMS, Celgene, Chugai, Eli Lilly, Genzyme, Janssen, MSD, Novartis, Pfizer Inc, Roche, UCB, J. Gomez-Reino Grant/research support from: AbbVie, MSD, Pfizer Inc and Roche, Consultant for: Pfizer Inc, Speakers bureau: AbbVie, Biogen, Bristol-Myers Squibb, Janssen, MSD, Pfizer Inc and Roche, P. Nash Grant/research support from: AbbVie, BMS, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant for: AbbVie, BMS, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Speakers bureau: AbbVie, BMS, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, D. Gladman Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, UCB, O. FitzGerald Grant/research support from: AbbVie, BMS, Novartis, Pfizer Inc, Consultant for: Amgen, Celgene, Eli Lilly, Janssen, C. Ritchlin Grant/research support from: AbbVie, Amgen and UCB, Consultant for: AbbVie, Amgen, Celgene, Janssen, Novartis, Pfizer Inc, Sun and UCB, E. Kudlacz Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Wu Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, A. Romero Shareholder of: Pfizer Inc, Employee of: Pfizer Inc